(untitled) (REMUNOM, 2025)
Thisstudyanalyzestheraw material acquisitionprocessandsupplychain management at Padaria Salubre, located in Sooretama-ES, Brazil. It adopts a qualitativeandexploratoryresearch approach, basedonsemi-structured interviews and direct observation, aimingtoidentifykeychallengesandproposeoperationalimprovements. The results show that, althoughthebakeryhasfunctionalpurchasingand stock management practices, its operations still relyon manual processes and informal supplierrelationships. The mainchallengesidentified include thelackofautomatedinventorycontrol, supplierconcentration, anddemandunpredictability. Recommendedimprovementsinvolveadopting FIFO and ABC Curve methodologies, implementingsimple digital systems for inventorycontrol, anddiversifyingsuppliers. Thesemeasuresaimtoreducewaste, optimizecosts, andincreaseoperationalefficiency, strengtheningthebakery’scompetitiveness in the regional market.